“Our fight is not [only] for land, it is for territory”: a proposal about protected areas from political ecology - Villas Boas, Guilherme Hissa; Vieira, Thiago Wentzel de Melo; Urzua, Victor Andres Niklitschek (Desenvolvimento e Meio Ambiente, 2025)
The creation of territories dedicated to the protection of biodiversity usually leads to land and territorial conflicts with historically marginalized social groups as it not only underestimates their ways of life, but also imposes forced expropriations. This work aims to reflect on the creation of Brazilian protected areas, based on the implications and consequences of the notions of nature in the National System of Conservation Units and to propose a new territorial framework that brings together, simultaneously, the protection of nature, land regularization , the autonomy and governance of traditional peoples and communities, as well as the democratization of access to natural resources, in a critical approach that goes beyond the issue of maintaining biodiversity itself. Legislation and legal regulations were revisited, as well as academic literature on the subject to prepare the analyses presented. In the first part, the text provides a historical overview of conservationist currents up to Brazilian socio-environmentalism. Next, it discusses the territorial effects of the application of law 9,985/2000 and its conceptions of nature. Subsequently, a reflection is elaborated, based on political ecology, on nature conservation and the need to incorporate cultural aspects into public environmental policies. With a propositional nature, arguments are presented for the creation of a new category of protected area: traditional territories. It is concluded that environmental conservation in Brazil in the 21st century must give up the nature-culture dichotomy to incorporate the concept of socio-biodiversity.